Analysis of the Mechanical Components Quality in Automotive Industry - Jacek Sitko (Communications of International Proceedings, 2021)
In the automotive industry effective the quality management is crucial and is regarding every enterprise in the long supply chain. As the producer formed and for the largest automotive concerns we regard car parts formed of best quality for the indicator of our action. In work, operations of the production of toothed bars used in the car steering mechanism have been described. The defects generated in the production process have been analysed. Using selected tools, the causes of defects have been identified and sorted in order to eliminate them. The raw material is from the warehouse to the production line delivered in a form of pinions. The process starts with a  grinder. After grinding, the parts are transported by conveyor belts to the milling machine. In this operation the teeth are milled. The subsequent stage involves degreasing the workpieces in the process of washing, cool the parts in the process of teeth milling,  impact on the quenched surface  the teeth from reaching the required hardness. The hardened bars are tempered in a furnace at 200ºC for 2h 30’. The aim of tempering is to get rid of stresses formed in  in the process of hardening. After tempering the bars are cooled in a cooling tunnel. After cooling, the parts are straightened by means of an automatic straightener so as to ensure their appropriate rectilinearity. At the end, final inspection is performed, the task of which is to check whether the parts have been made according to the customer’s requirements. In the destination of determining the scope of the impact of actions technological to the product quality and they used the process Pareto graph. He is based on an empirically discovered correctness, that in the human activity 20-30 % causes are usually responsible for 70-80 % effects. Due identifying responsible causes is an important issue too disagreements. The Pareto method is included in techniques which they let describe action being aimed at an improvement in processes and attributes of quality products and financial services. Studies have shown that during the research period of 6 months, it was found 449 mechanical defects, 320 crashes after milling, witch id due the technical reasons. The compliance of every element used for the production of the car with precisely determined norms and standards is in this case crucial, because a reliability and a safety of the ride are conditioning him. Produced according to increased norms to border possibilities and the subject for requiring examinations must meet the highest quality requirements. Getting the perfect compliance of the element with precisely determined parameters requires proper managing the processes associated with the quality of the production.
Keywords: Product; Quality; Defect; Automotive; Industry.